Functional results of AO 13C fractures managed with bicolumnar plating in a tertiary care centre of North India - Raina, Gagandeep Singh; Gupta, Sanjeev; Mahajan, Neeraj; Mahajan, Rahul; Lone, Zubair A. (International Journal of Research in Medical Sciences, 2021)
Background: Distal humerus fractures are associated with many problems like fracture comminution and complex fracture anatomy. Achieving a good functional range of motion at the elbow with stability are the primary objectives in managing a comminuted distal humerus fracture. Methods: 25 consecutive patients were operated with bicolumnar plating for fracture distal humerus AO type 13C. The patients were kept in follow up for at least six months. Mayo elbow performance (MEP) score and flexion extension arc was calculated to study the outcome. Results: All patients achieved fracture union with mean MEP score of 73.2 and mean flexion extension arc of 93º. This was within the functional range of elbow. Stiffness was observed to be most common complication. Conclusions: Our study concluded that internal fixation with bicolumnar plating offers good functional results in comminuted intra-articular fractures even in osteoporotic bone with negligible complications.